Carbon dissolution and segregation in Pd(110) - Bowker, Michael; Counsell, Jonathan; El-Abiary, Kareem; Gilbert, Lee; Morgan, Chris; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2010)
The bulk-surface diffusion of carbon in Pd(110) has been investigated using Molecular beams to examine the clean-off of carbon with gas-phase oxygen. The dominant product of the reaction above 600 K is CO CO, is only produced at much lower temperatures where the lifetime of adsorbed CO is significant. The segregation from the bulk Only Occurs at a measurable rate at >750 K, while loss of carbon into the bulk call occur at much lower temperatures. The reaction of carbon at high temperatures shows two regimes: (i) a non steady-state evolution of CO due to the clean-off of surface carbon already present on the surface, followed by (ii) a near steady-state reaction due to the continuous diffusion of carbon to the surface.